RECLAIMING NETWORKED SPACE THROUGH ALTERNATIVE MODELS OF CONNECTIVITY - Bain, Philip (AoIR Selected Papers of Internet Research, 2015)
The Internet, a product of many minds building upon the inventions of older minds, has been characterized as both a panacea and an instrument of oppression.But, like any tool, it is only as effective as the human beings who wield it. Recently there have been many hardware and software innovations used to create information networks that enhance and compliment the Internet. This research suggests that these alternative networking techniques have the power to promote digital democracy through challenging incumbent access providers by fostering community engagement and redefining our relationship with infrastructure.